RESPONS PERTUMBUHAN BIBIT KENTANG (Solanum tuberosum) TERHADAP FORMULASI BIOSTIMULAN BERBASIS Trichoderma spp. - Winda Nawfetrias; Dwi Pangesti Handayani; Irna Surya Bidara; Armelia Tanjung (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2019)
Growth Responses of Potato (Solanum tuberosum) Plantlets upon ApplicationÂ of Different Formulations of Trichoderma spp.-Based BiostimulantPlantlet acclimatization is one of several critical steps in potato clonal seedling production which often hampers the availability of quality plant materials. Application of biostimulant formulation containing Trichoderma spp. may increase growth capability of potato plantlets due to the improvement of plantlets in absorbing nutrient from the growth media. The aim of this research was to obtain the best formulations of biostimulant containing several strains of Trichoderma spp. to be applied in the acclimatization stage of potato seeds. Nine formulations of biostimulant (i.e. S1, S2, S3, S4, S5, S6, S7, S8, S9) each of which contained three to four different strains of five Trichoderma spp. isolates, were mixed with organic substrate carriers. The biostimulants were then applied to potato plantlets cv. Atlantic at the beginning of acclimatization. Plantlets without biostimulant were used as the control treatment (S0). The results showed that the S8 biostimulant formulation significantly increased the growth of the potato plantlets. The results of this experiment indicated that compared with the control and other formulations, the S8 biostimulant formulation significantly increased the growth of potato plantlets based on the number of leaves and number of shoots.Keywords: aclimatitation; biostimulant; potato; seedling; TrichodermaABSTRAKAklimatisasi planlet adalah salah satu tahapan kritis dalam produksi bibit klonal kentang yang seringkali menghambat ketercukupan bahan tanaman berkualitas. Penggunaan produk berbasis Trichoderma spp. diduga dapat meningkatkan kemampuan planlet untuk menyerap unsur hara dari media tumbuh. Tujuan penelitian ini adalah untuk mengetahui formulasi biostimulan terbaik yang mengandung Trichoderma spp. yang diaplikasikan pada tahap aklimatisasi bibit kentang. Sembilan biostimulan (S1, S2, S3, S4, S5, S6, S7, S8, S9) diformulasikan menggunakan substrat pembawa organik dan masing-masing mengandung campuran tiga atau empat strain dari lima isolat Trichoderma spp. Kesembilan biostimulan tersebut kemudian diujikan pada planlet kentang varietas Atlantik siap aklimatisasi. Planlet tanpa aplikasi biostimulan digunakan sebagai kontrol (S0). Hasil percobaan ini menunjukkan bahwa dibandingkan dengan control maupun formulasi lainnya, formulasi biostimulan S8 secara signifikan meningkatkan pertumbuhan planlet kentang cv. Atlantik dilihat dari jumlah daun dan jumlah tunasnya.